Estudo comparado das políticas indigenistas na fronteira Brasil-Guyana - Silva, Mariana Lima da (2016)
This dissertation aims to compare the Brazilian and Guyanese indigenous policies focused on land demarcation, self-sustain, education and social security. It has the intention of perceiving the relation between nationality and the access to these policies by transboundary indians, which ethnic territories has been overlapped by a national border. To do so, it was sought to comprehend the relations among the indigenous peoples in the historical context of Brazilian and Guyanese national State formation and the contemporary socioeconomic context of these countries in which take place the indigenous policies and the implications of nationality to access the national policies by transboundary indians.